2016
DOI: 10.1080/14767058.2016.1214126
|View full text |Cite
|
Sign up to set email alerts
|

The value of cardiovascular magnetic resonance in the diagnosis of fetal aortic arch anomalies

Abstract: Unlike prenatal Echo, fetal CMR is unaffected by fetal position. Fetal CMR with transverse views at the level of the aortic arch is a useful adjunct for the diagnosis of fetal aortic arch anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…We believe that fetal MRI is a useful adjunct for assessing the fetal anatomy, especially in cases of isolated aortic arch abnormalities. Li et al could show that fetal cardiovascular magnetic resonance (CMR) imaging, particularly with transverse views at the level of the aortic arch, in the diagnosis of aortic arch anomalies had an accuracy of 95.6% [4]. Fetal CMR is a promising diagnostic tool for assessment of congenital cardiovascular abnormalities, especially in situations that limit echocardiography [5].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that fetal MRI is a useful adjunct for assessing the fetal anatomy, especially in cases of isolated aortic arch abnormalities. Li et al could show that fetal cardiovascular magnetic resonance (CMR) imaging, particularly with transverse views at the level of the aortic arch, in the diagnosis of aortic arch anomalies had an accuracy of 95.6% [4]. Fetal CMR is a promising diagnostic tool for assessment of congenital cardiovascular abnormalities, especially in situations that limit echocardiography [5].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic role of fetal MRI, as a complementary second level tool useful when the ultrasound is hampered by inadequate acoustic window, has recently been proposed by several groups. 9,[38][39][40][41][42] In a prospective single-center study, a combination of SSFP and SS-T 2 -TSE sequences identified the same diagnosis as postnatal findings in 79% of fetuses with CHD at a mean gestational age of 25.5 weeks. 38 In that study the diagnostic sensitivity for cardiac anomalies by ultrasound screening performed by an obstetrician and by a fetal cardiac specialist were 46% and 82%, respectively.…”
Section: Complementary Diagnostic Role Of Fetal Cardiac Mrimentioning
confidence: 95%
“…However, it may be limited by fetal position, oligohydramnios, overlying bone, and obesity. The diagnostic role of fetal MRI, as a complementary second level tool useful when the ultrasound is hampered by inadequate acoustic window, has recently been proposed by several groups . In a prospective single‐center study, a combination of SSFP and SS‐T 2 ‐TSE sequences identified the same diagnosis as postnatal findings in 79% of fetuses with CHD at a mean gestational age of 25.5 weeks .…”
Section: Complementary Diagnostic Role Of Fetal Cardiac Mrimentioning
confidence: 99%
See 2 more Smart Citations